Primary urethral plasmacytoma treated with high-dose-rate brachytherapy: a case report - Stein, Johannes; Oelmann-Avendano, Jan Tobias (Urologia internationalis, 2016)
Primary urethral solitary plasmacytoma is a very rare variant of extramedullary plasmacytoma. In total, only 9 cases have been reported so far. Patients were treated either by surgery or by external radiation therapy. Here, we report on a 22-year-old man, initially presenting with a palpable induration at the penis, intermittent dysuria and haematospermia, which was due to histologically confirmed solitary urethral kappa-restricted plasmacytoma. The patient subsequently underwent percutaneous and endo-urethral high-dose-rate brachytherapy with a total dose of 42 Gy applied in 14 fractions. Besides an uncomplicated urinary tract infection and hyperpigmentation of the penis, the patient tolerated the radiotherapy well and is still free of disease after 15 months follow-up.